Productive losses on broiler preslaughter operations: effects of the distance from farms to abattoirs and of lairage time in a climatized holding area - Vieira,Frederico Márcio Corrêa (2010)
This work aimed to assess the effects of preslaughter lairage time on the welfare and mortality of broilers transported in different farm-abattoir distances. It was evaluated 215 poultry transport trucks from a commercial poultry slaughterhouse from 2006 to 2007. Data were obtained from the holding area acclimatized through fans and water misting in the mornings, afternoons and at night. The thermal variables (temperature and relative humidity), distance, lairage time and density of birds per cage were considered in the analysis. The effects of distance and lairage time were important in the variation of rectal temperature of the animals and on the number of dead animals per truck. Two models were developed (mean and dispersion), for each response variable in function of the interaction between lairage time and distance. As the lairage time in the holding area increased, the rectal temperature of the birds was reduced for all the studied distances. In farm-abattoir distances higher than 25 km, mortality was low when lairage time was lower than 1 hour. However, for distances below 25 km, in the same time interval, the number of dead birds was two-fold higher than in the first situation. The adjustment of lairage time has to be done accordingly to the distance provided that the lairage environment is correctly climatized.